Water and soil conservation techniques and food security in the northern region of Burkina Faso - Sanou, S.; Ayantunde, Augustine A.; Nianogo, A.J. (Academic Journals, 2018)
Food insecurity is a major challenge facing the rapidly growing population in the sub-Saharan Africa and it is a common feature in the northern region of Burkina Faso. The focus of this study was to investigate the prevalence of food insecurity in the northern region of Burkina Faso after many years of implementation of water and soil conservation techniques. A survey was carried out in six villages in the Northern Region of Burkina Faso involving 300 households to assess water and soil conservation techniques, and to examine the prevalence of food insecurity. The study was conducted between June and July 2015. Data collected was analyzed using logistic regression to identify factors influencing food insecurity in the study areas. The results also showed a high level of food insecurity affecting a large proportion of the population even during the post-harvest period when food was supposed to be available. Results showed that water and soil conservation techniques and household head education level were important factors in determining household food insecurity status. Despite the application of these techniques, food insecurity is still persistent, which raised questions about the efficiency of current agricultural production systems. In addressing food insecurity in the study area, it is necessary to reinforce the practice of combining stone bunds and inter-row ridges techniques along with proper use of fertilizer and manure. Given the persistent problem of water scarcity in Burkina Faso, and the relationship between water and food security, there is need to increase investment in water management infrastructures.